The theoretical basis of controlling in the public sector - E. A. Fedchenko; A. O. Buryakova (Вестник университета)
The article presents the results of scientific systematisation on the theory of controlling and analyses approaches of the Russian authors to the definition of controlling concept. In the course of the current study, the authors used methods of classification, mathematical modeling, grouping, and comparative analysis. On the basis of economic theory provisions, the authors proposed their own definitions of controlling, controlling system, subject area of controlling. Besides, certain ways to assess effectiveness of organisations’ work in the public sector were developed. Economic modeling was conductedwith consideration to existence of restrictions imposed on the objects of the study: the volume of goods produced is determined by target indicators, economic resources are limited by budgetary obligations. It has been established that efficiency of enterprises in the described sector is due to the volume ratio of input production factors (Cf) and produced economic goods (Qf). An increased zone of efficiency on the production flow chart of the variable pro duct and usage of these factors will indicate an enhanced productivity. In terms of the economic theory, improving effectiveness of implementation of measures is possible in the following cases: reduction in the cost of the used production factors, reduction of their volume, increase of the return on application of them (shifting the total product curve upwards).